2021
DOI: 10.1002/cnr2.1416
|View full text |Cite
|
Sign up to set email alerts
|

Conditional disease‐free survival rates and their associated determinants in patients with epithelial ovarian cancer: A 15‐year retrospective cohort study

Abstract: Background The most common type of ovarian cancer (OC) is epithelial ovarian cancer (EOC) which is the most lethal gynecologic malignancy in adult women. Aim This study aimed to determine the conditional disease‐free survival (CDFS) rates and their associated determinants in patients with EOC. Methods and results The clinical and demographic data of 335 patients with confirmed EOC at Motahari Clinic (Shiraz, Iran) were retrospectively reviewed and analyzed. Traditional DFS (TDFS) and CDFS were calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Ovarian cancer is the main cause of death from gynecologic tumors [18,19] as well as the ffth leading cause of cancer death in women [20]. Due to the anatomical characteristics of ovarian cancer, there are no specifc symptoms in its early stage and a lack of sensitive and specifc early screening methods [21], resulting in 70% of patients being diagnosed at an advanced stage [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is the main cause of death from gynecologic tumors [18,19] as well as the ffth leading cause of cancer death in women [20]. Due to the anatomical characteristics of ovarian cancer, there are no specifc symptoms in its early stage and a lack of sensitive and specifc early screening methods [21], resulting in 70% of patients being diagnosed at an advanced stage [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with type II EOC had a significantly higher incidence of advanced disease (FIGO stages III/IV) than type I patients (79.8% vs. 38% respectively) being the overall survival and progression-free survival significantly higher in patients with type I tumours [ 24 ]. In addition, some studies have found a markedly higher mortality in patients with advanced mucinous and clear cell carcinoma, compared to higher survival rates of patients with HGS-EOC and endometrioid subtypes [ 25 , 26 ].…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
“…According to literature, the rates of 5-year OS were estimated to be 20-35% for serous, 40-63% for endometrioid, 40-69% for mucinous, 35-50% for clear cell, and 11-29% for undifferentiated, respectively. [8][9][10][11] OCCC was less prevalent type, typically occurred at younger age, diagnosed at earlier stage; survival outcomes were generally favorable in the early stage, while advanced OCCC portended poor prognosis, which was often attributed to its inherent resistance to platinum-based chemotherapy. [12][13][14] Staging surgery or cytoreduction was recommended for OCCC, complete surgery with no macroscopic residual disease was the basis for survival benefit, was the most important prognostic factor for OCCC, even mini residual disease might significantly damage prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature, the rates of 5-year OS were estimated to be 20–35% for serous, 40–63% for endometrioid, 40–69% for mucinous, 35–50% for clear cell, and 11–29% for undifferentiated, respectively. 8 - 11 …”
Section: Introductionmentioning
confidence: 99%